Wobec mitów i faktów. Przedstawienia kolonii trędowatych na Spinalondze we współczesnej literaturze = Against myths and facts. Depictions of the leper colony on Spinalonga in contemporary literature - Wawryk, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the visualization of the leper colony on Spinalonga in the contemporary novels by Victoria Hislop (The Island, 2005) and Magda Knedler (Szepty z wyspy samotności [Whispers from the Island of Solitude], 2020), and in the reportage by Małgorzata Gołota (Spinalonga - wyspa trędowatych [Spinalonga - the Island of Lepers], 2021). The presented considerations are mainly literary in nature, but they also refer to other contexts related to the perception of leprosy over the centuries. A number of myths concerning this disease were perpetuated in literature, contributing to the exclusion of patients from society.
Keywords: Spinalonga; trąd; powieść obyczajowa; literatura faktu; Hislop, Victoria (brytyjska pisarka; 1959- ); Knedler, Magdalena (polska pisarka; 1983- ); Gołota, Małgorzata (1986- ); leprosy; fiction; non-fiction